Internal Fixation of Type I Capitellum Fracture with Headless Screws: A Case Report - Charlie Sanjaya; I Ketut Gede Arta Bujangga (Universitas Airlangga, 2021)
Background: Capitellum fractures are relatively rare. Distal humeral fractures that include capitellum and trochlea constitute approximately 6% of all distal humeral fractures and 1% of all elbow fractures. Despite the rarity of these injuries, an increasing number of clinical series have emerged, enhancing our understanding of these fractures.Case Report: A 26-year-old woman came to the emergency department with complaints of swelling and localized pain on the lateral side of her left elbow 2 hours after she fell off her motorcycle. Routine imaging such as plain radiographs and computed tomography scanning confirmed the fracture. She underwent open reduction and internal fixation surgery, stabilization of articular fragments with headless screws, and was fixated by a back slab and arm sling. The patient was also encouraged to do early elbow mobilization to avoid contractures and joint stiffness, routine follow-up every two weeks for a ROM evaluation. Preoperative Mayo Elbow-Performance Index score (MEPI) was 15, and postoperative 100.Discussion: The aim of capitellum fracture treatment is anatomical reconstruction and fixation to reduce the risk of non-union. In this case, we performed open reduction, secured two headless screws, which allow rigid fixation at the fracture site, provide fracture site compression through variable thread pitch design, and remained not removed later. These screws are suitable for use in anteroposterior and posteroanterior directions.Conclusion: The patient at two months follow-up has shown significant improvement. Accurate reduction, stable fracture fixation, and early postoperative mobilization were reported to provide good results with a MEPI score of 100.